The impact of intellectual capital on company value (Jurnal Manajemen Bisnis, 2021)
This study aims to analyze the partial effect of Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), Structural Capital Value Added (STVA) on Firm Value. is This research quantitative research. The research object is Property and Real Estate Companies listed on the Indonesia Stock Exchange (IDX) for 2015 to 2019 with a research sample of 18 companies that meet the criteria. Data The analysis using descriptive statistical techniques and Multiple Linear Regression aided by SPSS 25.0. The results showed that partially and simultaneously, VACA, VAHU, and STVA positively and significantly affect PBV